Peningkatan Keterampilan Wirausaha Siswa SMK NU Kedungtuban melalui Pelatihan Produksi, Pengemasan dan Penerapan Aplikasi Inventory - Stacia Reviany Mege; Anafil Windriya; Arkhan Subari (GOTAVA, 2023)
Mastery of entrepreneurship knowledge and skills is one of the objectives of holding a Business Center as a teaching factory from Kedungtuban NU Vocational High School. However, on the other hand, there are still a number of obstacles such as the lack of production and packaging facilities (equipment), as well as manual inventory management in stores which results in a lack of business center performance. The purpose of this community service is to improve the entrepreneurial skills of students at the NU Kedungtuban Vocational School, especially the Online Business and Marketing Department. The method in this activity is training with the concept of project-based learning. The results of this PkM activity are the renewal of production and packaging equipment and the existence of an inventory application for the Business Center. The training activities resulted in an increase in skills in production and packaging as well as the use of an inventory application of at least 80%. It can be concluded that the PkM activity target was achieved and the training methods and intensive mentoring used proved to be effective in improving skills.